Designing with the Brain in Mind: A Neuroaesthetic Pedagogy Framework - Fernández, Carlos; Nováková, Petra (University of Science and Computer Technology, 2026)
Contemporary graphic design education necessitates a deeper understanding of how aesthetic experience and cognitive processes shape creativity and empathetic comprehension in visual communication. Insights into how the brain perceptually and affectively interprets design can support the development of self-aware designers who respond more sensitively to human needs. Drawing on neuroaesthetics and design cognition, this study proposes an interdisciplinary approach that integrates creative pedagogy with the science of perception. This research introduces the Neuroaesthetic Pedagogy Framework (NPF) as an initial, exploratory framework that connects neurodesign principles with pedagogies of visual empathy and adopts an exploratory design-based research (DBR) methodology. Three iterative cycles were conducted as context-specific pedagogical interventions within a graphic design course, involving teaching experiments, reflective journals, and analyses of neuroaesthetic engagement. Thirty-eight undergraduate graphic design students participated over one semester, with observations focusing on cognitive and affective engagement in visual problem-solving activities. The findings suggest observable improvements in design cognition, particularly in visual reasoning and empathic decision-making, rather than statistically conclusive effects. The NPF indicates the potential to interconnect analytical and affective cognitive processes, supporting more emotionally informed design outcomes. This study concludes that the NPF demonstrates promise in bridging graphic design education and neuroscience by framing creative learning as an iterative process of aligning perception, cognition, and empathy, while highlighting the emerging importance of neuroaesthetic literacy in graphic design pedagogy.